1988
DOI: 10.1161/01.cir.77.3.552
|View full text |Cite
|
Sign up to set email alerts
|

Increased exercise ventilation in patients with chronic heart failure: intact ventilatory control despite hemodynamic and pulmonary abnormalities.

Abstract: This study was designed to determine the pathophysiologic basis of increased exercise ventilation in the presence of chronic heart failure. Sixty-four ambulatory patients with chronic heart failure and 38 age-matched normal control subjects performed exercise according to identical staged, symptom-limited bicycle exercise protocols with measurement of hemodynamic, ventilatory, and metabolic responses. Compared with normal subjects, ventilation and the ratio of ventilation to CO2 production (Ve/VC02), and pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
244
3
21

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(290 citation statements)
references
References 31 publications
(2 reference statements)
22
244
3
21
Order By: Relevance
“…Exercise hyperpnea correlates with ventilatory perfusion abnormalities and increasing physiological pulmonary dead space. 29 Because of left ventricular end-diastolic volume and pulmonary capillary wedge pressure are associated with CHF-CSAS, 26,27 and because of the presence of increased ventilatory perfusion abnormalities and physiological pulmonary dead space, the V…”
Section: Discussionmentioning
confidence: 99%
“…Exercise hyperpnea correlates with ventilatory perfusion abnormalities and increasing physiological pulmonary dead space. 29 Because of left ventricular end-diastolic volume and pulmonary capillary wedge pressure are associated with CHF-CSAS, 26,27 and because of the presence of increased ventilatory perfusion abnormalities and physiological pulmonary dead space, the V…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Because deteriorated alveolar hypoventilation rarely occurs in patients with heart failure, the cause of the augmented V…”
mentioning
confidence: 99%
“…Studies have found respiratory muscle weakness [3] and reduced respiratory muscle endurance [4] in patients with CHF. In addition, patients with heart failure show an increased ventilatory response to exercise [5], further exacerbating the imbalance between inspiratory muscle capacity and load. Therefore, it is reasonable to hypothesise that diaphragmatic fatigue may occur in patients with CHF when stressed by exercise.…”
mentioning
confidence: 99%